Psychrophilic anaerobic digestion of guinea pig manure in low-cost tubular digesters at high altitude - Garfí, Marianna; Ferrer Martí, Laia; Villegas, Vidal; Ferrer, Ivet (ELSEVIER, 2021)
Guinea pig is one of the most common livestock in rural communities of the Andes. The aim of this research was to study the anaerobic digestion of guinea pig manure in low-cost unheated tubular digesters at high altitude. To this end, the performance of two pilot digesters was monitored during 7 months; and two greenhouse designs were compared. In the dome roof digester the temperature and biogas production were significantly higher than in the shed roof digester. However, the biogas production rate was low (0.04 m(biogas)(3)m(digester)(-3) d(-1)), which is attributed to the low organic loading rate (0.6 kg(VS)m(digester)(-3)d(-1)) and temperature (23°C) of the system, among other factors. In a preliminary fertilization study, the potato yield per hectare was increased by 100% using the effluent as biofertilizer. Improving manure management techniques, increasing the organic loading rate and co digesting other substrates may be considered to enhance the process.